Studying and evaluating progressive collapse for an earthquake-resistant RC dual system according to columns and shear walls removal - Abdulhadi, Hasan (Latakia University Journal -Engineering Sciences Series, 2025)
Various types of buildings may be exposed to exceptional loading situations (earthquakes, explosions, fires, terrorist acts, etc.) that cause progressive collapse, which begins with a localized structural failure in specific structural elements, then a series of failures in the structural system that ends with collapse the entire building or large part of it, accompanied with human and material losses. The used design standards to mitigate the risks related to progressive collapse aim to use the continuity of structural elements and provide ductility, developing a good design plan that provides alternative load paths for the loads transferred from the damaged elements to the adjacent structural elements, which in turn must be able to bridging through this additional loads in order to prevent the collapse. The research results indicate that the earthquake-resistant dual systems (frames-shear walls) designed according to the Syrian Arab Code have good resistance against progressive collapse when removing columns and parts of shear walls according to US Department of Defense recommendations with specific local structural modifications to some of the main load-bearing elements.